PERAN EKSTRAKURIKULER KENTHONGAN DALAM MENUMBUHKAN CINTA TANAH AIR PADA SISWA MI MA’ARIF NU TELUK - Uswatun Khasanah; Pratik Hari Yuwono; Sony Irianto (Institut Pendidikan Tapanuli Selatan, 2020)
Cultural education is very important to be taught to young people today specifically. Cultural education can be taught through the school environment, both inside and outside the classroom. For learning cultural education outside the classroom can be taught through extracurricular activities. One of the extracurricular activities that can preserve the nation's culture is kenthongan. Kenthongan is one of the original arts of the Indonesian people. This research use desciptive qualitative approach. This study uses participants as principals, trainers, teachers, and students. Data collection is done through 1) Observation; 2) Interview; 3) Documentation. To test the validity of the data this study uses a triangulasih technique that compares and checks the truth of data information through observation, interviews, and documentation. Based on research results obtained that the state of extracurricular kenthongan is scheduled by the school on Friday. The kenthongan extracurricular is taught using the direct instruction method. The tools used for kenthongan activities are still complete, but there are some tools that have been damaged. There are two indicators of patriotism, namely pride in the work of Indonesia and preserving Indonesian culture. The inhibiting factor in kenthongan extracurricular activities is that the equipment used has begun to break down and the entry of foreign cultures. For supporting factors in kenthongan extracurricular activities, namely from schools and the environment.